TONI - One for all? Participatory development of a transtheoretic and transdiagnostic online intervention for blended care - S. Behr; F. Fenski; J. Boettcher; C. Knaevelsrud; L. Hammelrath; G. Kovacs; W. Schirmer; H. Petrick; P. Becker; C. Schaeuffele (Internet Interventions, 2024)
Background: Internet-based interventions offer a way to meet the high demand for psychological support. However, this setting also has disadvantages, such as the lack of personal contact and the limited ability to respond to crises. Blended care combines Internet-based interventions with face-to-face psychotherapy and merges the benefits of both settings. To ensure the uptake of blended care in routine care, Internet-based interventions need to be suitable for different therapeutic approaches and mental disorders. Objective: This paper describes the participatory development process of the Internet-based intervention “TONI” using a common therapeutic language and content on various transdiagnostic topics to be integrated into routine outpatient psychotherapy. Methods: To develop this intervention in a participatory manner, we followed the Integrate, Design, Assess, and Share (IDEAS) framework. In a multilevel development process, we used a combination of interviews, focus groups, and proofreading to optimally tailor online modules to routine outpatient psychotherapy. Building on well-established cognitive-behavioral online content, we included expert interviews with psychodynamic (n = 20) and systemic psychotherapists (n = 9) as well as focus groups with psychotherapists of different approaches (n = 10) and persons with lived experience of mental illness (PWLE; n = 10). Results: We describe the development process of TONI step-by-step, outlining the specific requirements that therapists from different therapeutic approaches as well as PWLE have and how we implemented them in our intervention. This includes the content and specific exercises in the online modules, aspects of data protection, language, design, and usability. Conclusion: Internet-based interventions that use a common therapeutic language and address therapeutic principles across different approaches have the potential to advance digitalization in psychotherapy. Involving psychotherapists and PWLE in intervention development may positively impact acceptance and usage in practice. This study shows how participatory intervention development involving both psychotherapists and PWLE can be carried out.